2021
DOI: 10.2151/sola.2021-004
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Possible Adaptation of Potato Production in Hokkaido to Climate Change Using a Large Number Ensemble Climate Dataset d4PDF

Abstract: This is a PDF of a manuscript that has been peer-reviewed and accepted for publication. As the article has not yet been formatted, copy edited or proofread, the final published version may be different from the early online release.This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Early seeding and planting can be an effective adaptive measure to global warming because it helps 1) decelerating the growth rate and guaranteeing the growth period under warmer conditions, and/or 2) avoiding growth retardation in hot summer caused by suppression of photosynthesis. Although Sugawara et al (2021) analyzed a projected reduction in potato yield under future climate and reported that 1-month-earlier planting did not mitigate the yield reduction in Hokkaido, it can still be a plausible adaptive approach. As well as the early planting in spring, delayed seeding for overwintering plants (e.g., winter wheat) may be effective (Dobor et al, 2016).…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Early seeding and planting can be an effective adaptive measure to global warming because it helps 1) decelerating the growth rate and guaranteeing the growth period under warmer conditions, and/or 2) avoiding growth retardation in hot summer caused by suppression of photosynthesis. Although Sugawara et al (2021) analyzed a projected reduction in potato yield under future climate and reported that 1-month-earlier planting did not mitigate the yield reduction in Hokkaido, it can still be a plausible adaptive approach. As well as the early planting in spring, delayed seeding for overwintering plants (e.g., winter wheat) may be effective (Dobor et al, 2016).…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Sprouting potatoes, or so-called volunteer potatoes, continue to increase during wheat cropping and become a source of renewal volunteer potatoes in the following year. High summer temperatures have reduced potato yields (Shimoda et al 2018a(Shimoda et al , 2023aSugawara et al 2021), and volunteer potatoes have S. Shimoda et al become a reservoir of disease and nematode infestation, reducing product quality and causing growers to lose their motivation to produce potatoes. The main method to control volunteer potatoes has been glyphosate-based herbicides, which are costly, ineffective, and not sustainable and have not been widely adopted in the region.…”
Section: Introductionmentioning
confidence: 99%